2014
DOI: 10.5539/cco.v3n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Four Week Hypofractionated Accelerated Intensity Modulated Radiotherapy and Synchronous Carboplatin or Cetuximab in Biologically Staged Oropharyngeal Carcinoma

Abstract: Hypofractionated accelerated chemoradiotherapy in the conformal era achieved acceptable control rates for squamous cell carcinoma of the head and neck. This study reports outcomes for biologically staged oropharyngeal cancer treated using four-week intensity-modulated radiotherapy (IMRT) and synchronous chemotherapy. Between 2009-2012, patients with squamous cell carcinoma of the oropharynx treated with hypofractionated chemo-IMRT (55Gray in 20 fractions), with either carboplatin or cetuximab were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Our data show that primary intensity‐modulated radiotherapy (IMRT) +/− chemotherapy is an effective treatment for squamous cell carcinoma of the oropharynx (OPSCC). We report similar rates of overall and disease‐free survival to those reported in many larger published case series in the literature (Table ) and also to historical published case series from the United Kingdom from the pre‐IMRT era . Our results add to the body of retrospective data that suggest inferiority of IMRT in terms of survival outcomes is unlikely .…”
Section: Discussionsupporting
confidence: 86%
“…Our data show that primary intensity‐modulated radiotherapy (IMRT) +/− chemotherapy is an effective treatment for squamous cell carcinoma of the oropharynx (OPSCC). We report similar rates of overall and disease‐free survival to those reported in many larger published case series in the literature (Table ) and also to historical published case series from the United Kingdom from the pre‐IMRT era . Our results add to the body of retrospective data that suggest inferiority of IMRT in terms of survival outcomes is unlikely .…”
Section: Discussionsupporting
confidence: 86%
“…For early larynx cancer (T1N0), 50 Gy/16 f was most commonly recommended, 8,9 and there are data for 55 Gy/20 f in T2N0 disease. 10,11 There is limited evidence to support the use of hypofractionated radical radiation therapy over 4 to 5 weeks for locoregionally advanced disease, but panelists suggested schedules, including 55 Gy/20 f, [12][13][14][15] 62.5-64 Gy/25 f, 16,17 and 54 Gy/18 f. 18,19 Most would not use concomitant chemotherapy in this setting, and there was agreement to restrict concomitant chemotherapy to schedules of 2.4 Gy/f. Although there are data to support the use of concomitant platinum chemotherapy with higher doses per fraction, 13,14,16 panelists expressed reservations about the potential lack of benefit (eg, no apparent local control or overall survival advantage from the combination of chemotherapy with accelerated radiation therapy) 20,21 and the risk of increased acute and late toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously conducted a phase IeII study of a 4 week non-doseescalated schedule to establish the safety of concurrent chemotherapy [22]. Literature-comparable outcomes using this approach with conventional techniques and with SIB IMRT in OPSCC have been reported [23,24]. However, this study is the first report of 5 week dose-escalated hypofractionated radiotherapy with chemotherapy in biologically selected OPSCC.…”
Section: Discussionmentioning
confidence: 97%
“…Hypofractionation has already been widely adopted in other areas, such as prostate and breast cancer, where trials showed equivalence [7,30]. Although 55 Gy in 20 fractions is safe and effective, the primary advantage is resource sparing, as radiobiological modelling does not predict improved local control [23,24,31].…”
Section: Discussionmentioning
confidence: 99%